Analyzing Prospects and Implications of CPEC on Baloch Imbroglio in Pakistan. (June 2023) - Kaur, Manjit; Malhi, Gurvel Singh
Baloch struggle is a long-drawn battle against the state of Pakistan and its mighty security establishment that has rather intensified by each passing day. The heightened ethnic consciousness and resolve to defend their homeland from the 'outsiders' have got a fillip with China Pakistan Economic Corridor (CPEC). The province of Balochistan has assumed strategic significance due to its location and natural resources. With the presence of China in the province, woes of Baloch nationalists have further grown. Pakistan will not let its control loose over the province and deepening ties with Beijing is reassuring for her. CPEC has increased existential difficulties for the Baloch people. In this context, the present article attempts to analyze the Baloch imbroglio as a struggle of the people of the province to protect their rights against the exploitation by the federal government in collaboration with a country which itself is rated as poor in terms of upholding human rights. It highlights the prospects of CPEC and its impact on the ongoing Baloch ethnic nationalism.